Marcel the shell with shoes on [videorecording (Blu-Ray)] - Disasterpeace (Musician), 1986- (A24, 2022)
Beloved online sensation, classic picture book character and now the star of a major motion picture, Marcel is an adorable one-inch-tall shell who ekes out a colorful existence. He wears a lentil as a hat and hang-glides on a Dorito, and though he may be small, he knows he has a lot of good qualities like his pretty awesome imagination -Amazon